The importance of early completion of cardiac investigations after ischaemic stroke: a case and systematic review of reperfusion therapy in stroke due to cardiac fibroelastoma. Issue 6 (2020) - Helliwell, Henrietta; Desai, Aishwarya; McCole, Mark; Beale, Andy; Ramadurai, Gopinath; Chandrasekaran, Badrinathan
No abstract available